2021
DOI: 10.1017/jfm.2021.542
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant convection in heterogeneous porous media with an inclined permeability jump: an experimental investigation of filling box-type flows

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Regimes (ii) and (iii) are respectively associated with the arrest and retraction of the gravity current front. Similar kinds of flow behaviour have been documented in the related studies of Goda & Sato (2011), Acton, Huppert & Worster (2001), Sahu & Flynn (2017) and Bharath, Sahu & Flynn (2020), who examined, theoretically and experimentally, distributed drainage over a deep lower layer having a relatively small permeability. Most notably, and consistent with Pritchard et al (2001) and Farcas & Woods (2009), these related studies found that gravity currents stop elongating when the rate of basal drainage from the gravity current underside matches the source influx.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Regimes (ii) and (iii) are respectively associated with the arrest and retraction of the gravity current front. Similar kinds of flow behaviour have been documented in the related studies of Goda & Sato (2011), Acton, Huppert & Worster (2001), Sahu & Flynn (2017) and Bharath, Sahu & Flynn (2020), who examined, theoretically and experimentally, distributed drainage over a deep lower layer having a relatively small permeability. Most notably, and consistent with Pritchard et al (2001) and Farcas & Woods (2009), these related studies found that gravity currents stop elongating when the rate of basal drainage from the gravity current underside matches the source influx.…”
Section: Introductionsupporting
confidence: 75%
“…The equivalence documented at the end of the previous paragraph runs contrary to the experimental observations of Bharath et al (2020). They studied gravity currents propagating along a permeability jump, and demonstrated that dispersion leads to enhanced gravity current elongation.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations